Outcomes of pulmonary resection in non-small cell lung cancer patients older than 70 years old - Apichat Tantraworasin (2019)
© 2019 Background: An appropriate treatment of older lung cancer patients has become an important issue. The aim of this study is to evaluate the short and long-term surgical outcomes in lung cancer patients using 70 years as a cut-point, and to identify prognostic factors of cancer-specific mortality in patients older than 70 years. Methods: Medical records of non-small cell lung cancer (NSCLC) patients who underwent pulmonary resection at Chiang Mai University Hospital from January 2002 through December 2016 were retrospectively reviewed. Patients were divided into age less than 70 years (control group) and 70 years or more (study group). Primary outcomes were major post-operative complications and in-hospital death (POM); secondary outcome was long-term survival. Multivariable regression analysis was used. Results: This study included 583 patients, 167 for study group, and 416 for control group. There were no differences in POM, both at univariable and multivariable analyses, however, for long-term cancer-specific mortality, the study group was more likely to die (HR adj = 1.40, 95%CI = 1.03–1.89). Adverse prognostic factors for long-term mortality in study group were having universal coverage scheme (HR adj = 1.70, 95%CI = 1.03–2.79), the presence of intratumoral lymphatic invasion (HR adj = 2.83, 95%CI = 1.28–6.29), perineural invasion (HR adj = 2.80, 95%CI = 1.13–6.94), underwent lymph node sampling (HR adj = 2.23, 95%CI = 1.16–4.30) and higher stage of disease (HR adj = 2.02, 95%CI = 1.06–3.85 for stage III, HR adj = 3.40, 95%CI = 1.29–8.94 for stage IV). Conclusions: In-hospital mortality and composite post-operative complications are acceptable in pulmonary resection for NSCLC patients older than 70 years. However, these patients had shorter long-term survival, especially who have some adverse prognostic factors. Further studies with larger sample size are warranted.